HPLC-MS İLE ELAZIĞ-ÖKÜZ GÖZÜ ÜZÜMLERİNDE FLAVONOİDLERİN TAYİNİ - POLAT, TAYFUN (Fırat Üniveristesi, 2017)
Bu çalışmada, Elazığ yöresine özgü olan öküz gözü üzümlerinde, antioksidan özellikleri bakımından önemli olanlardan kuersetin ve mirisetin bileşiklerinin tayini hedeflendi. Bu amaçla, üzüm örneklerinde kuersetin ve mirisetin bileşiklerinin tayini için metanol-askorbik asit-HCl çözücü karışımıyla ekstraksiyon yapıldı. Elde edilen ekstraktlardaki kuersetin ve mirisetin bileşikleri HPLC-MS yöntemiyle tayin edildi. HPLC-MS ile tayinde, enjeksiyon hacmi, akış hızı, fragmentasyon voltajı ve kolon sıcaklığı gibi parametrelerin optimum şartları uygulandı. 0.2-2 ppm aralığında farklı derişimlerdeki kuersetin ve mirisetin çözeltilerinin HPLC-MS ile analizi sonucu kalibrasyon grafikleri elde edildi. Gerekli hesaplamalar da yapılarak üzümlerde kuersetin ve mirisetin derişimleri hesaplandı. Sonuç olarak, 10 farklı noktadan toplanan üzümlerde kuersetin ve mirisetin bileşiklerinin miktarları sırasıyla 0.7-2.3 ve 0.5-1.1 ppm aralığında bulundu.

In this study, the determine of quercetin and myristine compounds in Okuzgozu grape being unique to Elazığ region were aimed, these components have high importance with regard to the antioxidant properties. For this purpose, the solvent mixture of methanol-ascorbic acid-HCl was used for the extraction of quercetin and myristicine compounds in grape samples. For for determination of quercetin and myristicine compounds in the obtained extracts, HPLC-MS device was used. In HPLC-MS determinations, the optimum conditions of parameters such as injection volume, flow rate, fragmentation voltage and column temperature were applied. Calibration graphs were obtained by analysis of quercetin and myristine solutions at different concentrations in range of 0.2-2.0 ppm, by HPLC-MS. quercetin and myristine concentrations in grapes were calculated from results of extractions and calibration graphs. As a result, the amounts of quercetin and myristate in the grapes collected from 10 different locations were found in range of 0.7-2.3 and 0.5-1.1 ppm, respectively.
Determination of flavonoids in Elazig-okuzgozu grape by HPLC-MS
Keywords: Kimya